ELEMENTS THAT CONTRIBUTE TO RESILIENCE IN YOUNG WOMEN FROM A HIGH-RISK COMMUNITY - Nadat, Yasin; Jacobs, Susanne (Social Work/Maatskaplike Werk, 2021)
This article reports on the elements contributing to the resilience of young women living in a high-risk urban community in the North-West province (NW) of South Africa who cope with various forms of adversity. Young Black Africans in South Africa face a myriad of, particularly in informal settlement communities. High-risk factors include psychosocial threats and structural adversity. A qualitative challenges descriptive approach using semi-structured interviews with 14 participants was utilized. Major findings indicated that religion is a protective factor fostering resilience. Strong altruistic tendencies, for instance, to serve as role models and peer mentors to other at-risk young women in the community were presented as internal assets. Maternal figures provide external social support. Communities and practitioners should monitor and make available opportunities for programmes and peer mentorship initiatives supporting the acquisition of personal and social assets, as well as for attaining goals that promote wellbeing of the young, particularly those who are disadvantaged. There should be more focus on cultural practices in research by social workers. This project contributes to South African research on indigenous studies.